A case study unpacking the collaborative research process: Eight essential components. Issue 131 (May 2022) - Wine, Osnat; Spiers, Jude; Kovacs Burns, Katharina; van Manen, Michael; Osornio Vargas, Alvaro
Abstract: Addressing complex environmental and health questions requires research collaborations. Such collaborations harness diverse expertise and perspectives from various researchers, practitioners, stakeholders, and knowledge-users to ground and enhance the depth and breadth of research and promote translational efforts towards policymaking. There is growing interest and need to understand what shapes these partnerships. Thus, our objective was to empirically identify the essential components of a collaborative research process. This qualitative case study followed a complex interdisciplinary research project over five years of operation. The project utilized an Integrated Knowledge Translation approach (IKT), a research partnership between researchers and knowledge-users. Data were generated through experiential interview/focus groups, surveys, and participant observation analyzed using inductive thematic analysis procedures. We identified eight essential components. The partnership evolved by building relationships, advancing individual growth, and building team capacity. These require the alignment of progress, knowledge, and expectations, establishing trust in each other, procedures, and outcomes, and developing shared ownership . Furthermore, operative elements and individual attitudes fostered the collaborative climate evolution. All components contributed directly and indirectly through complex interactions to shaping and maintaining the collaborative process and ultimately to growth, performance, co-production, and translational initiatives. At different times, the attainment or absence of these components facilitated or hindered the project's progression. This study provides an empiric in-depth description of the evolution of individual and collaborative team processes in which interdisciplinarity and IKT fostered co-production and knowledge translation. The evidence can serve as focal points to guide future planning and operation of research partnerships in different contexts. Graphical Abstract: ga1 Highlights: A qualitative case study exploring team processes in collaborative research. Eight components were essential for a successful research collaboration process. The components included dynamic team processes and enabling conditions. All components jointly evolved to reach optimal performance and productivity. Our empiric findings could serve as focal points for other research collaborations.